Determination of Meander Pattern in Gharehsou River Using Sinuosity Coefficients and Central Angle in Anzab-Samian Bridge reach - Fariba Esfandyari-darabad; Raoof Mostafazadeh; Ahmad Abyat; Ahmad Naseri (تحقیقات کاربردی علوم جغرافیایی)
Most of residential areas, population centers, and agricultural lands are located along the rivers and especially on the river terrace, which are affected by river dynamics, discharge changes, and flood hazards, bed fluctuations and meander variations. Therefore, it is necessary to study the behavior and pattern of meander movements of rivers in order to avoid potential hazards. The current research conducted in a reach of Gharehsou River in Ardebil province and the field measurements were done at adjacent to Anzab village to the Samian Bridge. In order to determine the pattern of this river, the Leopold Sinuosity Factor and the central angle calculated using Cornice method were used in this study. The results showed that the average of the Sinuosity Factor in the study area was 1.47, Which indicates the high ratio of river sinuosity. It also indicates the spatial variation of meanders evolution is not the same over the studied reach. The values of obtained Sinuosity factor using the employed methods showed that the %71.11 of meanders (32 meanders) with sinuosity factor of 1-1.5 belong to the category of low meander degree. While, the %17.78 of meanders (8 Meanders) had the sinuosity factor of 1.5-2. The remained 5 meanders (%11.11 of the identified meanders) had the sinuosity values greater than 2. This means that there are at least 5 meanders in the study area that are susceptible to becoming an oxbow-lake. Therefore, it is necessary to stabilize the stream banks and river bed of the study reach through structural management and engineering methods.